Simultaneous partial nitrification and 2-fluorophenol biodegradation with aerobic granular biomass: reactor performance and microbial communities - Ramos, Carlos (2017)
Supplementary data associated with this article can be found, in the online version, at: http://dx.doi.org/10.1016/j.biortech.2017.03.173.